Extraction of Lignin from Hemp Shives (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Industrial hemp contains 65-80% shives of the stalk and are composed of libriform fibres who are high lignin content. Steam explosion (SE) auto-hydrolysis is a simple treatment of biomass (agricultural waste, logging residues, etc.) by saturated only steam without any additional reagents, usually at pressures 32 atmospheres. This is the basic method how to produce lignin without any dash. Analogy if there is the most sever SE and more are destroyed hemp shives, the more lignin can extract. The aim is to definite the bulk volume, content of lignin in 'Belobrzesky' hemp variety depending on the SE treatment factor, doing extraction with H2O and NaOH 0.4% and compare without going content of hemp shives lignin.